DNA-segment-capture model for loop extrusion by structural maintenance of chromosome (SMC) protein complexes. Issue 13 (8th June 2019) - Marko, John F; De Los Rios, Paolo; Barducci, Alessandro; Gruber, Stephan
Abstract: Cells possess remarkable control of the folding and entanglement topology of long and flexible chromosomal DNA molecules. It is thought that structural maintenance of chromosome (SMC) protein complexes play a crucial role in this, by organizing long DNAs into series of loops. Experimental data suggest that SMC complexes are able to translocate on DNA, as well as pull out lengths of DNA via a 'loop extrusion' process. We describe a Brownian loop-capture-ratchet model for translocation and loop extrusion based on known structural, catalytic, and DNA-binding properties of the Bacillus subtilis SMC complex. Our model provides an example of a new class of molecular motor where large conformational fluctuations of the motor 'track'—in this case DNA—are involved in the basic translocation process. Quantitative analysis of our model leads to a series of predictions for the motor properties of SMC complexes, most strikingly a strong dependence of SMC translocation velocity and step size on tension in the DNA track that it is moving along, with 'stalling' occuring at subpiconewton tensions. We discuss how the same mechanism might be used by structurally related SMC complexes ( Escherichia coli MukBEF and eukaryote condensin, cohesin and SMC5/6) to organize genomic DNA.